Identification of compounds with activity against Trypanosoma cruzi within a collection of synthetic nucleoside analogs - Barnadas-Carceller, Berta; Martinez-Peinado, Nieves; Gómez, Laura Córdoba; Ros-Lucas, Albert; Gabaldón-Figueira, Juan Carlos; Diaz-Mochon, Juan J.; Gascon, Joaquim; Molina, Ignacio J.; Pineda de las Infantas y Villatoro, María José; Alonso-Padilla, Julio (Frontiers in Cellular and Infection Microbiology, 2023)
Chagas disease is caused by the protozoan parasite Trypanosoma cruzi, and it is arguably the most important neglected tropical disease in the Americas. Two drugs are available to treat the infection, but their efficacy is reduced in chronic stages of the disease, when most cases are diagnosed, and their tolerability is hindered by common adverse effects. Thus, the availability of safer and more efficacious antiparasitic drugs will mean a breakthrough for the control of the disease impact. From a target-based drug discovery approach, it has been shown that T. cruzi is unable to synthesize purines de novo and relies on a purine salvage pathway to acquire these from its host, making this an attractive target for the development of new therapies. In this study, we evaluated the anti-T. cruzi activity of 23 purine analogs with different substitutions in the complementary chains of their purine rings. We sequentially screened the compounds capacity to inhibit parasite growth, their toxicity in Vero and HepG2 cells, and their specific capacity to inhibit amastigote forms. Eight compounds showed specific antiparasitic activity with IC50 potencies ranging from 2.42 to 8.16 μM. Using in-silico docking we identified adenine phosphoribosyl transferase and hypoxanthine-guanine phosphoribosyl transferase as their susceptible main targets. Our results further illustrate the potential role the purine salvage pathway has as target route for the development of alternative treatments against T. cruzi infection.